1983
DOI: 10.3138/jcfs.14.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Equality and Violence Against Wives in American States

Abstract: The relationship between increasing sexual equality and the level of violence against wives has been the subject of some debate. A negative relationship has been posited by those who point out that as economic, educational, and legal opportunities and rights for women improve, fewer women remain trapped in violent marriages. Others have suggested that violence may increase as these social changes create additional strain and frustration for males attempting to retain their dominant position. This controversy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 0 publications
3
56
0
4
Order By: Relevance
“…A number of studies have demonstrated the effects of gendered social structures on state and national rates of domestic violence (e.g. , Levinson 1989;Yllö 1983) and on women's ability to escape from intimate terrorism (Anderson 2007). Finally, of course, we must not forget all of the evidence cited above that intimate terrorism is largely male-perpetrated, that violent resistance is primarily a woman's response to intimate terrorism, and that all types of intimate partner violence involve more injury, fear, and psychological damage when perpetrated by men rather than women.…”
Section: The Central Role Of Gender In Intimate Partner Violencementioning
confidence: 99%
“…A number of studies have demonstrated the effects of gendered social structures on state and national rates of domestic violence (e.g. , Levinson 1989;Yllö 1983) and on women's ability to escape from intimate terrorism (Anderson 2007). Finally, of course, we must not forget all of the evidence cited above that intimate terrorism is largely male-perpetrated, that violent resistance is primarily a woman's response to intimate terrorism, and that all types of intimate partner violence involve more injury, fear, and psychological damage when perpetrated by men rather than women.…”
Section: The Central Role Of Gender In Intimate Partner Violencementioning
confidence: 99%
“…With few exceptions (e.g., Yllo, 1983), little attention was paid to how structural or environmental factors may influence risk for IPV. In an effort to untangle the contributions of person and place to health disparities, a considerable amount of research over the past 2 decades has incorporated measures of neighborhood conditions or contexts into multilevel studies of various individual health risks and outcomes (see reviews in Diez Roux, 2000;Pickett and Pearl, 2001).…”
mentioning
confidence: 99%
“…11 13 14 Also, at the country level, gender inequality will be analysed as research has found that low egalitarianism as well as changes in gender norms toward a higher status of women in society are associated with higher rates of DVAW. [34][35][36][37] METHODS Data from the Eurobarometer 51.0 ''Europeans and their views on domestic violence against women'' was used for this study. It was carried out in 1999 and covered the population of residents 15 years and over in each of the member states of the EU at that time.…”
mentioning
confidence: 99%